Digital Learning Innovation: Mentoring to Improving Access to Education through ICT and Website-Based Media: Inovasi Pembelajaran Digital: Pendampingan untuk Meningkatkan Akses Pendidikan melalui Media Berbasis ICT dan Website - Ahmar, Dewi Satria; Rahmawati, Sitti; Ahmar, Ansari Saleh; Azzajjad, Muhammad Fath; Manalu, Yessi Febianti; Anisa, Nur (Mattawang: Jurnal Pengabdian Masyarakat, 2024)
The purpose of community service activities at SMAN 1 Sindue Tobata is to improve the quality of learning by providing training on how to create ICT-based learning media and websites. Schools that are far from Palu city center face difficulties in using technology in the education process. The program successfully improved teachers' understanding and skills by providing training on the use of information and communication technology. The results of the data analysis showed that the components of technology understanding, learning media creation skills, and website management each received excellent ratings, with an average of 3.36, 3.67, and 3.89, respectively. The results show that SMAN 1 Sindue Tobata experienced an improvement in the quality of education thanks to the training.